Light Microscopic Evaluation of the Effects of Experimental Partial Obstruction on the Ileum of the Lactating Rats - Helvacıoglu, Fatma; Erdoğan, Deniz; Elmas, Çiğdem (Fırat University, 2007)
Objectives: In this study, it was aimed to determine the ultrastructural alterations that may take place in the small intestines of rats that have undergone partial ileum obstruction on the 7th or 14th days of lactation. Material and Methods: Sprague-Dawley type pregnant rat were used. Experimental partial obstruction was apllied on the 7th (early period) day of lactation, on 14th (late period) day of lactation. Control group rats were also surgically operated but no obstruction was applied. On the 14th and 21st days following the obstruction; ileum samples of the both groups underwent routine electron microscobic examination. Semi thin sections were stained with toluidin blue and observed with microscope DM 4000 Leica analyzer light microscope. Results: When compared to the control group; at lactation period rats that underwent obstruction, loss of integrity was observed in the connective tissue and a large number of mast cells were seen nearby the epithelium. In addition there was a vasculation at the spaces adjacent to epithelium at late lactation period rats. After morphological examinations of the muscle wall thickness; we concluded that in early lactation period rat's muscle wall was 1.6 times thickened whereas at late lactation period thickening was 2.5 times more when compared to control group. These results were accepted as nonsense as a result of statistical analyses. .At morphometric studies of experimental groups; we observed that absorbative cells had hyperthrophy and as a result; cell number per unit area had decreased. Conclusion: As a result; we concluded that small intestine obstruction at lactation period caused morphological changes in epithelium, connective tissue and muscle layer. ©2007, Firat University, Medical Faculty

Giriş Bu çalışmada, bağırsak mukozasında birtakım değişikliklerin olaylandığı süt verme evresindeki sıçanların, ileumlarına uygulanan deneysel kısmi obstrüksiyonun, olası etkilerinin belirlenmesi amaçlandı. Gereç ve Yöntem: Çalışmada Spraque Dawley cinsi gebe sıçanlar kullanıldı. Süt verme evresinin 7. gününde (erken dönem) ve 14. (geç dönem) günlerinde deneysel kısmi bağırsak obstrüksiyonu uygulandı. Kontrol grubu deneklerde de cerrahi girişim aynen uygulanmakla birlikte obstrüksiyon gerçekleştirilmedi. Uygulamayı izleyen 14. ve 21. günlerde her iki gruba ait ileum doku örnekleri alışılmış elektron mikroskop izleme yöntemlerinden geçirildi. Yarı ince kesitler toluidin mavisi ile boyanarak DM 4000 Leica analyzer ışık mikroskobunda incelendi. Bulgular: Alınan yarı ince kesitler kontrol grubu ile karşılaştırıldığında, obstrüksiyon uygulanan süt verme evresindeki sıçanlarda, bağ dokusunda yer yer açılmalar, epitele yakın bölgelerde mast hücrelerinin yoğun olduğu izlendi. Ayrıca süt verme evresinin geç döneminde olan deney grubunda epitele yakın bölgelerde damarlanma dikkati çekti. Yapılan morfometrik değerlendirmelerde saf kontrol grubu ve deney grupları karşılaştırıldığında süt verme evresinin erken döneminde alınan doku örneklerinde kas katmanının 1.6 kat artığı, süt verme evresinin geç döneminde alınan doku örneklerinde ise kas katmanının 2.5 kat artmasına karşın istatistiksel olarak anlamlı olmadığı saptanmıştır. Sonuç: Süt verme evresinde uygulanan ince bağırsak obstrüksiyonun, ince bağırsakta epitel doku, bağ dokusunda ve kas katmanında yapısal değişikliklere neden olduğu kanısına varıldı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Süt Verme Evresindeki Sıçanlarda Deneysel Kısmi Obstrüksiyonunun İleuma Etkisinin Işık Mikroskop Düzeyinde Değerlendirilmesi